Organizational diagnosis through the SWOT matrix: the application of the tool in a Administration course (Research, Society and Development, 2021)
The present study sought to evaluate the factors that influence the Department of an Administration Course through the SWOT Matrix. In this way, it is possible to carry out an organizational diagnosis of the course's position in relation to the environment it is in, using the SWOT Matrix, which identifies four quadrants of possible action (survival, maintenance, growth and development) depending on the score obtained in its application. The study qualifies as a case study, of a descriptive nature, and quantitative and qualitative, where a questionnaire was applied with the managers of the Administration Department of the Advanced Campus Prof.ª Maria Elisa de Albuquerque Maia (CAMEAM) of the Universidade do Estado do Rio Grande do Norte (UERN). A scale similar to that used by Andrade et al., With a score of 1 to 3, was used to measure the importance factor of the variables listed in the questionnaire. The data were treated statistically and then a quantitative and qualitative analysis of the results was made. There was a need for the CAMEAM / UERN Administration Course to use mixed strategies due to the similarity of the scores obtained, but having to prioritize growth and opportunity strategies. Finally, it is admitted that the study is limited by the fact that it only considers information collected from the department's managers, and it is suggested to apply organizational diagnostic tools also with the students to outline a more assertive scenario of reality.